Triggering Oxygen Redox Cycles in Nickel Ferrite by Octahedral Geometry Engineering for Enhancing Oxygen Evolution - Yang Peng; Xu Zhao; Yiqun Shao; Xin Yue; Zhuofeng Hu; Shaoming Huang (Advanced Science)
Abstract Spinel‐type nickel ferrite (NixFe3‐xO4, x≤1) is a widely used electrocatalyst for the oxygen evolution reaction (OER). Due to the lower hybridization of metal‐d and oxygen‐p orbitals, the OER process on NixFe3‐xO4 follows the sluggish adsorbate evolution mechanism (AEM). Generally, activating the lattice oxygen to trigger the lattice‐oxygen‐mediated mechanism (LOM) can enhance the OER activity. Herein, to trigger the LOM pathway while maintaining high stability, iron foam (IF)‐supported Ni0.75Fe2.25O4 (NiFeO) with geometrical defects of [NiO6] (nickel cation coordinated with six oxygen anions) units and higher ratio of Fe to Ni cations in octahedral sites (d‐NiFeHRO/IF) is prepared by ion‐exchanging with polar aprotic solvent followed by annealing. As a result, as‐synthesized d‐NiFeHRO/IF exhibits excellent activity (at 295 mV overpotential to achieve 100 mA cm−2), fast kinetics (Tafel slope of only 34.6 mV dec−1), and high stability (maintaining a current density of 100 mA cm−2 over 130 h) for the OER. The theoretical calculations reveal that the construction of octahedral defect in NixFe3‐xO4 enhances the overlap of Fe‐d and O‐p orbitals, which can activate the lattice oxygen. Therefore, increasing the ratio of Fe to Ni will further improve the lattice oxygen redox activity, and thus trigger the fast LOM pathway, ultimately facilitating the OER process.